Deskripsi Penggunaan Media Pembelajaran dalam Kurikulum Merdeka Kelas V Sekolah Dasar Negeri 35 Pontianak Selatan - Jesse Herdiani; Siti Halidjah; Rio Pranata (Departement of Mathematics Education, 2024)
This study aims to describe the use of audio-visual learning media in Natural and Social Sciences (ESS) subjects in the independent curriculum and evaluate its effectiveness in improving students' understanding, engagement, and motivation. The methods used in this research are observation and interviews with teachers and students in several schools. The results showed that audio-visual media, such as documentary videos, animations, and interactive slide presentations, helped teachers deliver subject matter in a more interesting and understandable way. Students showed increased interest and enthusiasm, as well as better understanding of the material presented. Teachers felt that the media made it easier to explain abstract concepts, while students revealed that learning became more enjoyable and they remembered the material more easily. The conclusion of this study is that the use of audio-visual learning media is effective in improving the quality of learning.